2012
DOI: 10.1093/cvr/cvs278
|View full text |Cite
|
Sign up to set email alerts
|

Induction of intracellular heat-shock protein 72 prevents the development of vascular smooth muscle cell calcification

Abstract: Our study shows for the first time that intracellular HSP72 may function as a central regulator of molecular pathways involved in the development of VC. We suggest treatment strategies that up-regulate HSP72 as a new approach to inhibit VC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 36 publications
(31 reference statements)
2
10
0
Order By: Relevance
“…Furthermore, the low expression of HSP70 in the arterial wall is associated with an increased risk of vascular calcification (Lu et al. 2012 ). However, it was also reported that extracellular HSP70 could promote BMP2/4-induced cell condensation and osteogenic differentiation in calcifying vascular cells by binding with matrix GLA protein (Yao et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the low expression of HSP70 in the arterial wall is associated with an increased risk of vascular calcification (Lu et al. 2012 ). However, it was also reported that extracellular HSP70 could promote BMP2/4-induced cell condensation and osteogenic differentiation in calcifying vascular cells by binding with matrix GLA protein (Yao et al.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of HSP70 is compromised in CKD patients with coronary artery disease (CAD), and induction of intracellular HSP70 could prevent the development of VSMC calcification (Lu et al. 2012 ). Downregulation of HSP90 was also found in calcified aortic valves, suggesting HSP90 as a central signalling molecule in aortic valvular calcification (Weisell et al.…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al demonstrated that HSP72 induction can prevent the development of vascular calcification in human aortic smooth muscle cells [104]. Vascular calcification is correlated with cardiovascular mortality and is commonly observed in patients with coronary artery disease and CKD initiated by CRS type 4 [105,106].…”
Section: Role Of Hsps In Cardiorenal Syndromementioning
confidence: 99%
“…To date, in vitro and in vivo experiments have tested 12 natural antioxidants that are also dietary ingredients, including 10-dehydrogingerdione (10-DHGD) 64 , apocynin 18,19 , curcumin 38 , diosgenin 20,21 , ellagic acid 56 , gallic acid 48 , gingko biloba extracts 50 , puerarin 62 , quercetin 2531 , resveratrol 52 , silybin 38 , and vitamin E 34,35 . Among these compounds, apocynin, diosgenin, quercetin, and vitamin E have been shown by multiple studies to have anti-VC properties.…”
Section: Antioxidants From Natural and Dietary Sources For Treatment mentioning
confidence: 99%
“…It has been extensively investigated with respect to its effect against VC based on our literature search results. Lu et al disclosed that quercetin abolished heat shock protein 72 induced anti-calcification effect in vitro and ex vivo 25 ; however, another group later found that quercetin completely nullified warfarin-induced aortic calcification and aortic medial cartilaginous metaplasia by inhibiting transglutaminase 2 and β-catenin expression in vitro 2628 . Alternatively, quercetin could reduce aortic calcification in CKD rats partially by increasing superoxide dismutase 2 (SOD2) levels and modulating the inducible NO synthase (iNOS)/MAPK pathway 29 .…”
Section: Antioxidants From Natural and Dietary Sources For Treatment mentioning
confidence: 99%